2003
DOI: 10.1056/nejm200301093480218
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir Disoproxil Fumarate in Patients with HIV and Lamivudine-Resistant Hepatitis B Virus

Abstract: The new england journal of medicine n engl j med 348;2 www.nejm.org january 9, 2003 170 correspondence Prostatectomy or Watchful Waiting in Prostate Cancer to the editor: In their article comparing prostatectomy with watchful waiting, Holmberg et al. (Sept. 12 issue) 1 present their analysis according to the intention-to-treat principle, but the true treatment effect might be larger than that observed because of noncompliance with the protocol. 2 Presentation of information on the outcome in the participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
79
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(85 citation statements)
references
References 3 publications
4
79
0
2
Order By: Relevance
“…A similar decrease in serum HBV DNA of 3.5 and 3.9 log 10 genome equivalents/ml was demonstrated in two other studies after 48 weeks of treatment with ADV (20,51). Tenofovir disoproxil fumarate (TDF), a nucleotide analog approved for the therapy of infection with human immunodeficiency virus (HIV), was also effective in HBV-infected patients who developed 3TC resistance (5,7,43,45,50,59,61,63). Treatment with TDF for 24 to 71 weeks in HIV-coinfected patients demonstrated that HBV DNA concentrations decreased by approximately 4 to 5 log 10 genome equivalents/ml on average (5,18,31,43,45,50,62,63).…”
supporting
confidence: 55%
“…A similar decrease in serum HBV DNA of 3.5 and 3.9 log 10 genome equivalents/ml was demonstrated in two other studies after 48 weeks of treatment with ADV (20,51). Tenofovir disoproxil fumarate (TDF), a nucleotide analog approved for the therapy of infection with human immunodeficiency virus (HIV), was also effective in HBV-infected patients who developed 3TC resistance (5,7,43,45,50,59,61,63). Treatment with TDF for 24 to 71 weeks in HIV-coinfected patients demonstrated that HBV DNA concentrations decreased by approximately 4 to 5 log 10 genome equivalents/ml on average (5,18,31,43,45,50,62,63).…”
supporting
confidence: 55%
“…Long-term lamivudine therapy (more than 100 weeks) leads to HBeAg seroconversion in 27% of individuals but has also been associated with the frequent development of drug resistance (39,40). Other nucleotide RTI, such as adefovir [9-(2-phosphonylmethoxyethyl)adenine] and tenofovir [9-(R)-(2-phosphonyl-methoxypropyl)adenine], and the nucleoside RTI entecavir (formerly BMS-200475, a carbocyclic 2Ј-deoxyguanosine analog) have also been shown to be effective against HBV (1,6,23). Tenofovir is often used in combination with lamivudine for effective treatment of HBV in HIV-1-infected individuals, as both agents are active against HIV-1 as well as HBV.…”
mentioning
confidence: 99%
“…These results are similar to those reported in the literature from studies conducted in healthcare settings that were not resource-limited. [10][11][12][13][14][15][16] The TDF/lamivudine-based treatment was adequately effective against HIV replication. Although a large proportion of patients had undetectable HIV RNA, especially HBeA − patients, one-third of the patients studied were not successfully treated.…”
Section: Discussionmentioning
confidence: 99%
“…TDF anti-HBV efficacy in HIV-co-infected patients has been reported only in relatively small studies with relatively short durations of therapy. [10][11][12][13][14][15][16] Recommendations for the treatment of HBV in HIV co-infected patients are derived from what is known about the treatment of HBV monoinfected patients, and from the limited data available in HBV/HIV co-infected patients. 9 The most recent WHO recommendation regarding antiretroviral therapy (ART) for HBV/HIV co-infection is based on a limited and questionable body of evidence, and the panel that issued the guideline was able to identify only one randomized controlled trial on TDF effectiveness in HBV/HIV co-infection.…”
Section: Introductionmentioning
confidence: 99%